John F. Dillon, The Revised Ordinances of the City of Davenport, Revised and Digested by Order of the City Council, Containing the Original and Amended City Charters, with Notes and References to Judicial Decisions Page 145 (1866) Ch. 19, § 1-2 - (:unkn) unknown (General Publisher, 1855)
Prohibited discharge of any gun, pistol, or other firearms. Also prohibited discharging firecrackers, rockets, or any other description of fireworks. Violators fined not less than two nor more than ten dollars for each offense.
--
Keywords: DISCHARGE